Resibufogenin and Cinobufagin Activate Central Neurons through an Ouabain-Like Action - Wang, Ze-Jun; Sun, Liqin; Heinbockel, Thomas (PLOS ONE, 2014)
Cinobufagin and resibufogenin are two major effective bufadienolides of Chan su (toad venom), which is a Chinese medicine obtained from the skin venom gland of toads and is used as a cardiotonic and central nervous system (CNS) respiratory agent, an analgesic and anesthetic, and as a remedy for ulcers. Many clinical cases showed that Chan su has severe side-effects on the CNS, causing shortness of breath, breathlessness, seizure, coma and cardiac arrhythmia. We used whole-cell recordings from brain slices to determine the effects of bufadienolides on excitability of a principal neuron in main olfactory bulb (MOB), mitral cells (MCs), and the cellular mechanism underlying the excitation. At higher concentrations, cinobufagin and resibufogenin induced irreversible over-excitation of MCs indicating a toxic effect. At lower concentrations, they concentration-dependently increased spontaneous firing rate, depolarized the membrane potential of MCs, and elicited inward currents. The excitatory effects were due to a direct action on MCs rather than an indirect phasic action. Bufadienolides and ouabain had similar effects on firing of MCs which suggested that bufadienolides activated neuron through a ouabain-like effect, most likely by inhibiting Na+/K+-ATPase. The direct action of bufadienolide on brain Na+ channels was tested by recordings from stably Nav1.2-transfected cells. Bufadienolides failed to make significant changes of the main properties of Nav1.2 channels in current amplitude, current-voltage (I-V) relationships, activation and inactivation. Our results suggest that inhibition of Na+/K+-ATPase may be involved in both the pharmacological and toxic effects of bufadienolide-evoked CNS excitation.